COMPARATIVE ANALYSIS OF PHENOTYPIC CHANGES OF ADIPOSE TISSUE AND BONE MARROW CELL CULTURES IN THE COURSE OF CULTIVATION - Ковпак, В. В.; Ковпак, О. С. (Scientific Progress & Innovations, 2017)
This article describes the changes in phenotype of cultures of adipose tissue cells (ATCC) and bone marrow cells (BMCC) in the process of cultivation. Study of primary cultures of cells of the bone marrow and adipose tissue of rat has shown that they are morphologically heterogeneous, they included: a small number of cells of polygonal shape, and the bulk was fìbroblast-like cells. Process of transition from the heterogeneous cultures at zero passaging to the most homogeneous at the end of the study was noted during further cultivation. We noted differences in immunophenotype of bone marrow and adipose tissue cell cultures that did not disappear with passaging.